Reporting threats of terrorism: stigmatisation, procedural justice and policing Muslims in Australia - Murphy, Kristina (Policing and society, 2020)
The increase in Islamic-inspired terrorism on Western soil has led governments around the world to introduce new counter-terrorism laws and more intrusive police practices aimed at countering the threat of terrorism. This has had a profound negative impact on Muslim communities living in the West who have expressed feeling stigmatised by institutional responses to terrorism. Such feelings of stigmatisation have implications for Muslims’ willingness to work collaboratively with authorities to counter terrorism. Using survey data collected from 800 Muslims living in Australia, the current study investigates whether Muslims’ perceptions of procedural justice policing can mitigate the effect of feeling stigmatised on their willingness to report terror threats to authorities. We find that both lower levels of stigmatisation and positive perceptions of procedural justice policing are associated with Muslims’ greater willingness to report terrorism threats to police. However, we also find that procedural justice moderates the relationship between feeling stigmatised and reporting intentions. Specifically, procedural justice has a stronger positive effect on reporting intentions for those Muslims who feel more stigmatised. In other words, highly stigmatised Muslims place more salience on procedural justice when deciding whether to report information to police. The implications of these findings for theory and police practice are discussed.